Increased activation-induced cell death of high IFN-gamma-producing T(H)1 cells as a mechanism of T(H)2 predominance in atopic diseases - AKKOÇ, TUNÇ (MOSBY-ELSEVIER, 2008)
Background: A dysregulated and T(H)2-biased immune response appears to be a key pathogenetic factor in atopic diseases. Increased activation and massive infiltration of T cells in the dermis without any evidence for the expansion of their numbers in peripheral blood characterize atopic dermatitis. Objective: To investigate differences and mechanisms of T(H)1 and T(H)2 cell activation-induced cell death (AICD) in atopic disease. Methods: Naive (CD4(+)CD45(+)RA) and memory (CD4(+)CD45(+)RO) T cells were isolated from healthy and atopic individuals. T(H)1 and T(H)2 subsets were in vitro differentiated. High IFN-gamma-producing T cells and CXCR3(+) T cells were purified, and AICD of isolated cells was determined in addition to expression of apoptosis receptors and caspase activation. Results: T(H)1 cells, particularly their high IFN-gamma-producing fraction, and CXCR3(+) T cells showed significantly increased apoptosis in atopic individuals. During their in vitro differentiation, both T(H)1 and T(H)2 cells of atopic individuals showed increased apoptosis compared with the healthy control group, with a significantly high apoptosis in T(H)1 cells. Increased expression of Fas, Fas-ligand, tumor necrosis factor receptor-H, and caspase activation was detected on T(H)1 cells that underwent apoptosis. Neutralization experiments demonstrated a dominant role of IFN-gamma and Fas-Fas-ligand interaction-mediated suicide in T(H)1 cell AICD. Conclusion: Predominant T(H)2 profile in atopic diseases might be a result of the increased tendency to activation and apoptosis of high IFN-gamma-producing T(H)1 cells.
Keywords: T cells; activation-induced cell death; apoptosis; atopy; T(H)1 cells; CXCR3; FAS/FASL-MEDIATED APOPTOSIS; SELECTIVE UP-REGULATION; MATURE T-CELLS; CYTOKINE PRODUCTION; ALLERGIC DISEASE; TH2 CELLS; DERMATITIS; KERATINOCYTES; LYMPHOCYTES; EOSINOPHILIA